Temperature Insensitive Strain Sensor with Asymmetrical Cascading Structure Based on Photonic Crystal Fiber in Chemical Corrosion. (19th November 2017) - Fu, Guangwei; Li, Yunpu; Yang, Jiandong; Li, Qifeng; Fu, Xinghu; Bi, Weihong
Abstract : In this paper, a corroded photonic crystal fiber (PCF) sensor is presented on the basis of core-offset splicing and waist-enlarged fiber taper corroded by hydrofluoric acid (HF). The Mach-Zehnder interference theory is used to analyze the relationship between transmission spectrum and strain. The final results obtained from experiments show that the strain sensor's sensitivity is about −6.57 pm/ με and the linearity is 0.99962 within the range of 0~1000  με, while the sensor is corroded by HF for 35 minutes at room temperature. In the temperature range of 20°C~80°C, the sensor's sensitivity to temperature is only 1.63 pm/°C, which is insensitive to temperature. Because of its advantage compared to traditional optical fiber sensors, this sensor can avert the cross-sensitive problem when temperature and strain are measured together and has some other advantages including easily fabricated, simple structure and accurate sensitivity. It can be used in many fields, such as industrial production, monitoring, and aerospace.